Analysis of a mathematical model for brain lactate kinetics - Carole Guillevin; Rémy Guillevin; Alain Miranville; Angélique Perrillat-Mercerot (Mathematical Biosciences and Engineering)
The aim of this article is to study the well-posedness and properties of a fast-slow system which is related with brain lactate kinetics. In particular, we prove the existence and uniqueness of nonnegative solutions and obtain linear stability results. We also give numerical simulations with different values of the small parameter $ε$ and compare them with experimental data.